Points to consider for laboratories reporting results from diagnostic genomic sequencing. (January 2018) - Vears, D.; Sénécal, K.; Clarke, A.; Jackson, L.; Laberge, A.; Lovrecic, L.; Piton, A.; Gassen, K.; Yntema, H.; Knoppers, B.; Borry, P.
Abstract Although NGS technologies are well-embedded in the clinical setting for identification of genetic causes of disease, guidelines issued by professional bodies are inconsistent regarding some aspects of reporting results. Most recommendations do not give detailed guidance about whether variants of uncertain significance (VUS) should be reported by laboratory personnel to clinicians, and give conflicting messages regarding whether unsolicited findings (UF) should be reported. There are also differences both in their recommendations regarding whether actively searching for secondary findings (SF) is appropriate, and in the extent to which they address the duty (or lack thereof) to reanalyse variants when new information arises. An interdisciplinary working group considered the current guidelines, their own experiences, and data from a recent qualitative study to develop a set ofpoints to consider for laboratories reporting results from diagnostic NGS. These points to consider fall under six categories: (i) Testing approaches and technologies used, (ii) Approaches for VUS; (iii) Approaches for reporting UF, (iv) Approaches regarding SF; (v) Reanalysis of data & re-contact; and vi) Minors. While it is unclear whether uniformity in reporting across all laboratories is desirable, we hope these points to consider will be useful to diagnostic laboratories as they develop their processes for making decisions about reporting VUS and UF from NGS in the diagnostic context.